Uncovering the Path to Successful Digital Performance through Digital Technology and Digital Culture as Moderation - Junaedi, Achmad Tavip; Renaldo, Nicholas; Yovita, Indri; Augustine, Yvonne; Veronica, Kristy (International Conference on Business Management and Accounting, 2023)
The main aim of the research is to detail the relationship between digital technology adoption and corporate performance indicators, paying particular attention to the way digital culture plays a key moderating role in this process. This research was conducted qualitatively through surveys and interviews. The informants used in this research were 3 informants. Survey and interview results show a large variety of answers from informants. From the results of the interviews, the dimensions and indicators forming the variables of digital technology, digital culture, and digital performance were obtained. A deep understanding of the complex relationship between digital technology, company performance, and digital culture is a key foundation for developing effective strategies. Digital technology influences digital performance, digital culture influences digital performance, and digital culture moderates the influence of digital technology on digital performance, respectively qualitatively. Companies are recommended to provide in-depth education and training to employees on the use of digital technology and its impact on company culture. Encourage employee acceptance and active involvement in digital transformation.